Analisis Disiplin Kerja pada PT. Voksel Electric Tbk. - Mahesa Dimyati Haryo Kasemen,; Christian Wiradendi Wolor,; Marsofiyati Marsofiyati, (Jurnal Publikasi Ilmu Manajemen, 2023)
This research aims to comprehensively understand the work discipline system at PT. Voksel Electric Tbk. This research aims to find out how companies manage employee work discipline using a qualitative case study approach for one month in 2023. Data was collected through observation, interviews and documentation from four HR informants. These findings highlight the need to improve work discipline, especially regarding employee tardiness. Companies already have regulations and sanctions, but enforcement is still difficult. In this research, it was found that PT. Voksel Electric Tbk. has work policies and regulations that cover various aspects of work discipline, including provisions related to tardiness, working hours and dress codes. However, there are still obstacles in implementing work discipline, especially related to late arrival of employees.